2012
DOI: 10.6002/ect.2012.0080
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory and Anti-Inflammatory Cytokine Balance in Patients With Cirrhotic Hepatitis During Live-Donor Liver Transplant

Abstract: Objectives: The immune system releases cytokines during the stress response, and the balance between proinflammatory and anti-inflammatory cytokines is important. This prospective study was done to determine which cytokines are responsible for maintaining cytokine balance during live-donor liver transplant surgery. Materials and Methods: Recipients undergoing livedonor liver transplant surgery due to cirrhotic hepatitis were allocated to a recipient group (n=44), and healthy donors were placed in the donor gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…6 The imbalance between pro-inflammatory and antiinflammatory parameters is responsible for the susceptibility to and outcome of sepsis. 7 By increasing oxidative stress and reactive oxygen species (ROS), the body's antioxidant system is impaired, leading to effects on the cells and mitochondria and finally causing organ dysfunction. 8 To investigate the pathogenesis of sepsis and its mechanisms, three methods are usually utilized: 1) injection and using lipopolysaccharides (LPS) and other exogenous toxin like zymogens; 2) applying different fatal and vivid pathogens; 3) elimination or changing the endogenous protective barrier, like cecal ligation and puncture (CLP) and colon ascendens stent peritonitis.…”
Section: Introductionmentioning
confidence: 99%
“…6 The imbalance between pro-inflammatory and antiinflammatory parameters is responsible for the susceptibility to and outcome of sepsis. 7 By increasing oxidative stress and reactive oxygen species (ROS), the body's antioxidant system is impaired, leading to effects on the cells and mitochondria and finally causing organ dysfunction. 8 To investigate the pathogenesis of sepsis and its mechanisms, three methods are usually utilized: 1) injection and using lipopolysaccharides (LPS) and other exogenous toxin like zymogens; 2) applying different fatal and vivid pathogens; 3) elimination or changing the endogenous protective barrier, like cecal ligation and puncture (CLP) and colon ascendens stent peritonitis.…”
Section: Introductionmentioning
confidence: 99%
“…Koh et al 9 performed a study regarding this issue and demonstrated this condition. Their results showed that the cytokines released markedly in patients with cirrhotic hepatitis during liver transplant surgery include IL-6 (a pro-inflammatory cytokine whose concentration increased as much as 40 times compared to its preoperative values at the anhepatic stage) and IL-10 (an anti-inflammatory cytokine whose concentration was 60 times higher than its preoperative value at the neohepatic phase) (Table 1).…”
Section: Pro-inflammatory and Anti-inflammatory Cytokine Balance Durimentioning
confidence: 93%
“…Previous studies on cytokines secretion related to liver transplantation in patients with liver failure mostly focused on the types and subtypes of cytokines secreted during each stage of surgery 3, the serial changes in their concentrations during the surgery 4, and their relation to postoperative outcome after transplantation 5, 6. Additionally, several studies to elucidate the following issues have been done; factors influencing the secretion of cytokines during liver transplantation 7, 8, pro-inflammatory and anti-inflammatory cytokine balance during liver transplantation surgery 9, and the changes in the ratio of T helper 1 (Th 1) to T helper 2 (Th 2), and T helper 17 (Th 17) to regulatory T (Treg) cell signature cytokines during liver transplantation surgery with tools to change on the levels of Th 1, Th 2, Th17 and Treg cell signature cytokines 10. In this review article, we aim to introduce these studies regarding cytokines secretion during liver transplantation and to suggest study directions for better outcomes of the patients.…”
Section: Introductionmentioning
confidence: 99%